Shifting ecologies of malignant and nonmalignant cells following BRAF inhibition - Wu, Catherine J. (The Journal of Clinical Investigation, 2014)
Clinical vignette: A 49-year-old man with stage IV BRAFV600E-driven melanoma was initiated on twice-daily 960 mg of vemurafenib for treatment of progressive and recurrent subcutaneous metastatic disease of the left lower extremity. The patient’s melanoma responded well to targeted BRAF inhibition. At treatment onset, hematologic parameters were all within normal limits; however, within three months of initiating therapy, wbc were found to be elevated (to 20 K) with sustained lymphocytosis of mature phenotype. Immunophenotypic analysis was consistent with chronic lymphocytic leukemia (CLL), and FISH results revealed presence of the CLL-associated deletion in chromosome 13q14 as well as in 2p33. Vemurafenib was withdrawn after approximately one year of therapy, and subsequently, his peripheral lymphocytosis resolved and CLL regressed. Nevertheless, a monoclonal B cell population persisted even 732 days after discontinuation of vemurafenib.